Efficient frequency-domain detection for massive MIMO systems - Cabral, L. (2017)
Reduced-complexity implementations are critical for massive MIMO (Multiple Input, Multiple Output) systems. In this paper we consider the uplink of broadband massive MIMO systems employing SC-FDE (Single-Carrier with Frequency-Domain Equalization) schemes, where multiple users transmit to a single base station with a large number of antennas. We propose low-complexity frequency-domain detection schemes that allow excellent performance, but do not require matrix inversions.